Association between Peak Neutrophil Count, Clopidogrel Loading Dose, and Left Ventricular Systolic Function in Patients with Primary Percutaneous Coronary Intervention. (24th July 2014) - Wang, Xinyu; Yu, Haiyi; Li, Zhaoping; Li, Liuning; Zhang, Youyi; Gao, Wei
Abstract : Inflammation plays an important role in plaque development and left ventricular remodeling during acute myocardial infarction (AMI). Clopidogrel may exhibit some anti-inflammatory properties and high loading dose of clopidogrel results in improved clinical outcomes in patients with AMI. 357 patients who received successful primary percutaneous coronary intervention from January 2008 to March 2011 in Peking University Third Hospital were included in this study. Different loading dose of clopidogrel (300 mg, 450 mg, or 600 mg) was given at the discretion of the clinician. Neutrophils reached their peak values on the first day after AMI. Higher levels of peak neutrophil and lower left ventricular ejection fraction (LVEF) were found in patients of low clopidogrel loading dose group (300 mg or 450 mg). After adjusting for the related confounders, a logistic regression model showed that low clopidogrel loading dose remained an independent predictor of low LVEF (LVEF ≤ 50%) [OR: 1.97, 95% CI: 1.03–3.79, P = 0.04]. Low clopidogrel loading dose was associated with higher peak neutrophil count and poor left ventricular systolic function, suggesting an important role of clopidogrel loading dose in the improvement of left ventricular function and high loading dose may exhibit better anti-inflammatory properties.